Radiation induced vesicovaginal fistula - Tiwari, Kenusha Devi (Nepal Journal of Obstetrics and Gynaecology, 2018)
Case: A 63 years old female visited our outpatient department for involuntary loss of urine per vagina since 1.5 year. She had undergone radical hysterectomy and radiotherapy 16 years ago for cervical carcinoma. With positive dye test, on examination she had vesicovaginal fistula with Goh classification of 2biii. She underwent fistula repair via vaginal approach. After 3 weeks of catheterization, successful closure was achieved. Radiation therapy is an effective treatment for cervical cancer. However, of various complications, irradiation sometimes cause the formation of fistula between vagina and bladder and or rectum compromising the quality of life. Pelvic radiation is the primary cause of delayed vesicovaginal fistula with incidence of 13%. Majority of them become apparent 1.5-2 year after termination of radiotherapy and can occur even up-to 20-30 years after the original insult. Keywords: cervical cancer, fistula, radiation induced